2011
DOI: 10.1007/s10265-011-0405-2
|View full text |Cite
|
Sign up to set email alerts
|

More nitrogen partition in structural proteins and decreased photosynthetic nitrogen-use efficiency of Pinus massoniana under in situ polluted stress

Abstract: Masson pine (Pinus massoniana L.) trees in the Pearl River Delta have shown growth decline since late 1980s, particularly those around industrially polluted regions. As nitrogen is an important nutritional element composing functional proteins, structural proteins and photosynthetic machinery, investigation on nitrogen allocation is helpful to understand nutrient alteration and its regulation mechanism in response to pollution stress. Current year (C) and 1-year old needles (C + 1) of five mature trees were sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 47 publications
1
19
1
Order By: Relevance
“…Takashima et al (2004) estimated 55% and 65% nitrogen partitioning (assuming 5% nitrogen partitioning to respiratory mitochondrial enzymes) to FIG. The large percentage of total leaf nitrogen in the residual pool is hypothesized to be used in structural (cell wall) proteins (6-14%; Takashima et al 2004, Guan andWen 2011), other nitrogen proteins (i.e., proteins not invested in photosynthesis, respiration, and structure; 15-25% after subtracting 5% mitochondrial proteins; Chapin et al 1987, Takashima et al 2004, free amino acids (2.5%; Chapin et al 1987), lipids (3-4%;Chapin et al 1986), nucleic acids (8.5-15%;Chapin et al 1986, Chapin 1989, Evans and Seemann 1989, and CO 2 fixation proteins (other than Rubisco; 4%; Chapin et al 1987). The correlations between fractional leaf nitrogen allocation pools, photosynthesis parameters, and leaf nitrogen for all plant functional types combined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Takashima et al (2004) estimated 55% and 65% nitrogen partitioning (assuming 5% nitrogen partitioning to respiratory mitochondrial enzymes) to FIG. The large percentage of total leaf nitrogen in the residual pool is hypothesized to be used in structural (cell wall) proteins (6-14%; Takashima et al 2004, Guan andWen 2011), other nitrogen proteins (i.e., proteins not invested in photosynthesis, respiration, and structure; 15-25% after subtracting 5% mitochondrial proteins; Chapin et al 1987, Takashima et al 2004, free amino acids (2.5%; Chapin et al 1987), lipids (3-4%;Chapin et al 1986), nucleic acids (8.5-15%;Chapin et al 1986, Chapin 1989, Evans and Seemann 1989, and CO 2 fixation proteins (other than Rubisco; 4%; Chapin et al 1987). The correlations between fractional leaf nitrogen allocation pools, photosynthesis parameters, and leaf nitrogen for all plant functional types combined.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf nitrogen varies with environmental conditions, leaf traits, and geographic location (Reich et al 1992, Reich and Oleksyn 2004, Wright et al 2004, and is correlated with photosynthetic parameters (Wullschleger 1993, Xu and Baldocchi 2003, Coste et al 2005, Grassi et al 2005. However these studies relied on a few measurements (i.e., data at only three sites) for evaluating the behavior of their optimal nitrogen allocation model (e.g., Xu et al 2012), considered limited PFTs (mostly short-lived non-woody plants or woody juveniles) that lacked explicit representation of interspecies difference in nitrogen allocation (e.g., Chapin et al 1986, Evans 1989, Makino and Osmond 1991, Onoda et al 2004, Takashima et al 2004, Guan and Wen 2011, or did not consider nitrogen allocation for a complete range of processes including carboxylation, light harvesting, bioenergetics, maintenance respiration, and growth respiration (e.g., Coste et al 2005, Delagrange 2011. However these studies relied on a few measurements (i.e., data at only three sites) for evaluating the behavior of their optimal nitrogen allocation model (e.g., Xu et al 2012), considered limited PFTs (mostly short-lived non-woody plants or woody juveniles) that lacked explicit representation of interspecies difference in nitrogen allocation (e.g., Chapin et al 1986, Evans 1989, Makino and Osmond 1991, Onoda et al 2004, Takashima et al 2004, Guan and Wen 2011, or did not consider nitrogen allocation for a complete range of processes including carboxylation, light harvesting, bioenergetics, maintenance respiration, and growth respiration (e.g., Coste et al 2005, Delagrange 2011.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The deposition of atmospheric sulfur, nitrogen, and industrial dust containing metals has caused the decline of indigenous tree species in South China, but the mechanisms are incompletely understood5625. Our previous studies indicated that different forms of pollutants, alone or in combinations, are involved in accelerating oxidative process, causing decreased rates of electron transport and damaged membrane systems in leaf cells256.…”
mentioning
confidence: 99%